الطلاق البدعيأضراره الدينية و الاجتماعيةدراسة تحليلة نقديةرسالة مقدمة لنيل درجة الماجستير في الفقه و أصولهقسم الشريعة الإسلامية بجامعة سوراكرتا المحمديةSinful Practice of Divorce - The Danger Seen From Religious and Social Aspects - Al Mishry, Yusuf Muhammad Ahmad Saleh (2014)
This study is library study dan qualitatif Study, it used the method analysis of critical study. The case of Sinful Practice of Divorce. The condition of old case. The discussed problems in this Study cover several things and the several most important things are: : 1. What's the intial law of Thalaq : is it permissible or forbidden ? 2. How about the law for make triple divorce all at once? 3. How to interpret The conduct of Shahabah Umar R.a. while determined that triple divorce in one time means triple divorce? 4.Why did it occurred some divorce cases during the period of Prophet Muhammad PBUH ? because sinful practice of divorce has been done? 5. what are the dangers of divorce practice seeing from religious and social aspects? After reviewing and examines the related events and review the existing provisions and opinions of Islamic scholars/ the Ulema, obtained the following result : 1. Originally, divorce is forbidden, so that, before doing divorce, must fulfilled restrictions and etiquette. 2. Doing triple divorce in one time is rejected and bid'ah, because it is contrary to Al Qur'an and Sunnah. 3. The conduct of Umar Ra. is regulation and syaria wisdom because of specific problem of ummah 4. The main factor of the divorce spread is doing the practice of sinful divorce. 5. the dangers of sinful practice of divorce practice seeing from religious and social aspects is : a. it is bid'ah, b. make a women forbidden for his husband and permissible for the other men, spread of divorce practice, the growing number of divorce women, the large burden for ummah and the ignoring children. It requires the Ulema to prohibit sinful practice of divorce and get back to the origin.